EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521062 ZenodoArchiveConcept: 7521061 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521062 10.53832/edtechhub.0145 2405685:M3D6NGR4 2405685:WVRHTVIZ 2486141:V94NMZIU
Keywords: _r:AddedByZotZen

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6929534 10.53832/edtechhub.0123 2339240:7VEG4LSW 2405685:R4E96T5V 2405685:T9NZ63T3 2405685:VSHH2JUL
Keywords: _r:AddedByZotZen

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14967648 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1098 ZenodoArchiveConcept: 14967647
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A review of existing guidance and minimum standards - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Hayat, Amal; Emerusenge, Aime Parfait; Zazai, Rozina (EdTech Hub, 2024)
EdTech Hub is seeking to work with the education in emergencies (EiE) sector to develop quality standards and guidance relating to the effective implementation of educational technology (EdTech) in crisis contexts. To ensure that this work is genuinely meaningful and helpful, it is important to understand what guidance is already available in this space, and what effective guidance could look like. To do this, we reviewed existing guidance documents relating to the design and implementation of EdTech in emergency contexts, along with materials from adjacent disciplines such as humanitarian work and technology design and development. By identifying key commonalities and persistent gaps across these documents, we were able to suggest what future guidance relating to EdTech in emergencies should include, and how this guidance should be developed. Keywords: EdTech; education in emergencies; guidance; minimum standards An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14051241 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1068 ZenodoArchiveConcept: 14051240
Keywords: _r:AddedByMyEducationEvidence

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652130 previousZenodoArchiveID: 3830953 previousshortDOI: 10/ghgk68 previousDOI: 10.5281/zenodo.3830953 shortDOI: 10/ghgk68 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3830953 10.53832/edtechhub.0033 10/ghgk68 2339240:XCBTX2XL 2405685:2HM2SBVM 2405685:FU7Z8QM7
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11235144 ZenodoArchiveConcept: 11235143 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1029 10.53832/edtechhub.1030
Keywords: _r:AddedByMyEducationEvidence

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

Education in Emergencies: A Rapid Evidence Review - Mitchell, Joel; Ashlee, Amy; Clericetti, Giulia; Gladwell, Jessica; Torrance, Rebecca (EdTech Hub)
PreviousDOI: 10.5281/zenodo.4476897 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4476897 10.5281/zenodo.4556940 2339240:GU8FEH69 2339240:W9GJBGT9 2405685:FEXJQ37Q 2405685:ZPTMAP5C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521375 ZenodoArchiveConcept: 7521374 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521375 10.53832/edtechhub.0154 2405685:AHVWDNGT
Keywords: _r:AddedByZotZen

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
ZenodoArchiveID: 4140412 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4140412 2129771:9X3BTTLU 2339240:9PYYNK6J 2405685:ISTFVCA7 2405685:NS927T5K
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8208265 ZenodoArchiveConcept: 8208264 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8208265 10.53832/edtechhub.0057 10.53832/edtechhub.0173 2405685:47KMRR48 2405685:N2E79MUD
Keywords: _r:AddedByZotZen